THE USE OF DIGITAL TOOLS FOR ENHANCING GRAMMATICAL COMPETENCE OF THE FUTURE ENGLISH PHILOLOGISTS - Burtnyk, Bohdana (Primedia E-launch LLC, 2021)
There is a widespread belief that the interaction between a teacher and a student in the lesson is impossible without digital tools, which give the opportunity to make any lesson more interactive and understandable, especially in the digital era. The integration of digital resources into all aspects of a modern teacher's life elicits new approaches to the organization of educational processes. The present article tries to shed a light on this issue. For this reason, a few resources and their usage have been exemplified.
Keywords: grammar; grammatical competence; methodology; digital tools